«The Great Protector of Wits». D’Holbach 1789-2019. 9-11th May 2019, Göttingen, Lichtenberg-Kolleg. Conference Report - Galvagni, Enrico (Diciottesimo Secolo, 2020)
This is a report of the first ever International Conference fully devoted to Baron d’Holbach (1723-1789). Entitled «“The Great Protector of Wits”. D’Holbach 1789-2019», this event was organized by Laura Nicolì and Franziska Meier and held from 9-11th May 2019 at the Lichtenberg-Kolleg, The Göttingen Institute for Advanced Study. The conference was organized into eight subsequent sessions and two roundtables and aimed to explore every aspect of Baron d’Holbach’s polymorphic intellectual activity. This report will highlight the structure of the conference, pointing out the main traits of every contribution.